2019
DOI: 10.1103/physrevd.100.113006
|View full text |Cite
|
Sign up to set email alerts
|

CP asymmetry in τKSπντ decays within the standard model and beyond

Abstract: This work aims to explore the 2.8σ discrepancy observed between the BaBar measurement and the Standard Model prediction of the CP asymmetry in τ → K S πν τ decays. Firstly, we reproduce the known CP asymmetry due to K 0 −K 0 mixing by means of the reciprocal basis, which is convenient when a K S(L) is involved in the final state. As the Kπ tensor form factor plays a crucial role in generating an extra direct CP asymmetry that can arise only from the interference of vector and tensor operators, we then present … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 157 publications
(416 reference statements)
1
49
0
Order By: Relevance
“…The value of Λ 2 has been determined in ref. [87]: Λ 2 = (11.1 ± 0.4) MeV (see also [88]). If we assume resonance saturation, we can, in fact, use this relation to get a value for the coupling…”
Section: Jhep01(2021)059mentioning
confidence: 91%
“…The value of Λ 2 has been determined in ref. [87]: Λ 2 = (11.1 ± 0.4) MeV (see also [88]). If we assume resonance saturation, we can, in fact, use this relation to get a value for the coupling…”
Section: Jhep01(2021)059mentioning
confidence: 91%
“…Here we shall investigate for the first time whether an observable CP asymmetry in the angular distribution of τ → K S πν τ decays could be generated by the well-measured CP violation in K 0 −K 0 mixing. To this end, we shall employ the reciprocal basis [40][41][42][43][44][45], which is most convenient when a K S(L) is involved in the final state and has been used to reproduce conveniently the decay-rate asymmetry [33]. It is then found that a non-zero CP asymmetry would appear in the angular observable of the decays considered, even within the SM.…”
Section: Jhep05(2020)151mentioning
confidence: 99%
“…While the formalism of the former is quite clear [43], a precise description of the latter requires information about the Kπ vector and scalar form factors, including both their moduli and phases. As the form-factor phases fitted via a superposition of Breit-Wigner functions with complex coefficients do not vanish at threshold and violate Watson's final-state interaction theorem before the higher resonances start to play an effect [31][32][33], we cannot rely on the formalism developed in refs. [46][47][48][49] the CP asymmetry in τ → K S πν τ decays.…”
Section: Jhep05(2020)151mentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent works [16][17][18][19][20] have put forward that semileptonic tau decays offer also an interesting scenario to set bounds on nonstandard weak charged current interactions complementary to other low-energy semileptonic probes considered before, such as nuclear beta decays, purely leptonic lepton, pion, and kaon decays or hyperon decays (see, e.g., Refs. [21][22][23][24][25][26][27][28][29][30][31]).…”
Section: Introductionmentioning
confidence: 99%